Prevalence, diagnosis and management of mastitis in dairy cattle under field conditions - CHAND, N; Kumar, S; Soni, Y K; Pande, Megha; Prasad, Naresh; Saha, S (Indian Farming, 2019)
Mastitis is a serious problem in dairy animals as it is an economically devastating disease causing immense economic losses to the dairy industry in India. Sub-clinical mastitis (SCM) is a major cause of economic loss in dairy herds. It is more prevalent than the clinical mastitis, it reduces milk production and adversely affects milk quality. Sub-clinical mastitis causes more economic losses than clinical mastitis. The prevalence of mastitis in dairy cows is highly variable, with an incidence ranging from 5 to 50%. Subclinical mastitis causes 10-25% loss in milk production whereas in clinical mastitis there may be total loss of milk. Production of high quality milk requires an efficient mastitis control programme. Herds with a high prevalence of mastitis are incapable of producing high quality milk until the inflammation and infection in the udder are brought under control. Effective control of mastitis in dairy animals includes prompt treatment of clinical cases of mastitis, use of cow-side diagnostic test to diagnose subclinical cases of mastitis in dairy herd, use of post-milking teat dips, dry therapy, maintenance of cleanliness and hygiene in the animal premises and adequate nutrition to the dairy animals.